Use of Microbes for the Alleviation of Soil Stresses, Volume 1 - Miransari, Mohammad (Springer New York : Imprint: Springer, 2014)
Use of Microbes for the Alleviation of Soil Stresses, Volume 1 describes the most important details and advances related to the alleviation of soil stresses by soil microbes. Comprised of seven chapters, the book reviews the mechanisms by which plant growth promoting rhizobacteria (PGPR) alleviate plant growth under stress; the role of mycorrhizal fungi on the alleviation of drought stress in host plants; how PGPR may alleviate salinity stress on the growth of host plants; and the role of PGPR on the growth of the host plant under the stress of sub optimal root zone temperature.   Written by experts in their respective fields, Use of Microbes for the Alleviation of Soil Stresses, Volume 1 is a comprehensive and valuable resource for researchers and students interested in the field of microbiology and soil stresses.